Health Coverage and Financial Protection in Uganda: A Political Economy Perspective - Maria Nannini; Mario Biggeri; Giovanni Putoto (Kerman University of Medical Sciences, 2022)
Background  As countries health financing policies supporting progress towards Universal Health Coverage (UHC), an analysis of these policies is particularly relevant in Low and Middle-Income Countries (LMICs). In 2001, the government of Uganda abolished user-fees to improve accessibility to health services for the population. However, after almost 20 years, the incidence of catastrophic health expenditures is still very high, and the health financing system does not provide a pooled prepayment scheme at national level such as an integrated health insurance scheme. Objective  This article aims at analysing the Ugandan experience of health financing reforms with a specific focus on financial protection. Financial protection represents a key pillar of UHC and has been central to health systems reforms even before the launch of the UHC definition.   Methods  The qualitative study adopts a political economy perspective and it is based on a desk review of relevant documents and a multi-level stakeholder analysis based on 60 Key Informant Interviews in the health sector. Results  We find that the current political situation is not yet conducive for implementing a universal health coverage system with widespread financial protection: dominant interests and ideologies do not create a net incentive to implement a comprehensive scheme for this purpose. The health financing landscape remains extremely fragmented, and community-based initiatives to improve health coverage are not supported by a clear government stewardship. Conclusion  By examining the negotiation process for health financing reforms through a political economy perspective, this article intends to advance the debate about politically-tenable strategies for achieving UHC and widespread financial protection for the population in LMICs.